Five new species of Oedogonium Link (Chlorophyta), a freshwater filamentous algae from Nepal - Raj, Shiva Kumar (Nepalese Journal of Biosciences, 2013)
The present paper deals with six species of genus Oedogonium Link, among which five species are being recorded for the first time from Nepal. They are Oedogonium leave Wittrock, O. peipingense Jao, O. pisanum Wittrock, O. plagiostomum Wittrock and O. undulatum (Bréb.) A. Braun in De Bary. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7485 Nepalese Journal of Biosciences 2 : 17-23 (2012)